Elements of Iconicity in the Texts of Antanas A. Jonynas - Butnoriūtė, Neringa (Colloquia, 2017)
The author of this article presents, and examines the expression of, iconicity in the poetry of Antanas A. Jonynas. Drawing on the American semiotician Charles S. Peirce’s sign theory and hermeneutic analysis she reveals how, in Jonynas’s poetry, reality is contextualized through language – its characteristics, expression, and meaning. Unusually for Lithuanian literary studies, the article dicsusses iconicity in terms of cognitive poetics.The article relates poetic expression with both iconicity in language and the function of metaphor within the literary text. These reflect the complex phenomenon of literary visualization and convey the fundamental human ability to think in terms of analogy.As is characteristic for modern poets, Jonynas stresses the importance of language: it is a means, a separate motive, and a problematized aesthetic effect – it is the power to both create a world and to decipher human experience through language. The image of reality within the text is based on the logic of spectacle (the analysis reveals the latter’s metatextual status), and for this reason the drama of the poem can appear to be both real and theatrical. But Jonynas’s texts are characterized by the ability to simultaneously talk about and describe states, and to convince and engage the perceiver: the texts combine sensations and draw on the transmission function (speaking and listening). The author of the article offers a detailed analysis of the nature of the poet’s language and the motif of memory in his writing. Images and the entire texts’s metaphoric level reveal the discontinuity between conscious speaking and nondiscursive experience in Jonynas’s poetry. The poetic text combines elements of reality; existential categories merely create the misleading impression that the status of emotion in the text is equivalent to the represented object or landscape.
Keywords: Antanas A. Jonynas; Lithuanian poetry; iconicity; icon; metaphor